Determining poverty impacts on Lao People's Democratic Republic and Cambodia: Reconciling household and GTAP data - Ginalyn Komoto; Susan Stone (Asian Development Bank Institute (ADBI), 2009)
Poverty-related studies are usually general examinations of the impact of policy reforms or major investments on the poor. However, policy changes may have varying consequences across different segments of the poor. To more accurately determine the poverty implications of policy initiatives, it is important to stratify households according to income source and decompose their factor earnings. This paper applies a method that builds consistency between information in the Lao People's Democratic Republic (PDR) and Cambodian household surveys, and the outputs of the general equilibrium model developed at the Global Trade Analysis Project, or GTAP model. This allows for a consistent platform for translating policy changes to changes in poverty headcount across income strata. Thus, changes in sector outcomes arising from policy reforms or major investments (such as infrastructure projects) can be traced through changes in factor incomes. From there, a connection can be drawn between improvements in sector-specific outcomes and movements of people in and out of poverty. As such, this method will help ensure effective policy design when the objective is poverty reduction. This method can be readily extended to other developing countries' survey data.
Keywords: I32; O2; 330